Spatial patterns of local species richness reveal importance of frugivores for tropical forest diversity. (20th November 2017) - Chanthorn, Wirong; Wiegand, Thorsten; Getzin, Stephan; Brockelman, Warren Y.; Nathalang, Anuttara
Abstract: Seed dispersal by frugivores, particularly primates, plays an important role in structuring and maintaining tree diversity in tropical forests. However, little is known about the effect of frugivores on the diversity of saplings and large trees. We used detailed census data from the fully mapped 30‐ha Mo Singto forest dynamics plot in Thailand together with spatial point pattern analysis to find out if the local species richness of small (dbh <10 cm) and large (dbh ≥10 cm) trees in the neighbourhood of large trees of 52 focal species was larger or smaller than expected by an appropriate null model. We then used binary data (+ or 0) on the seed dispersal network at the Mo Singto plot to test the hypothesis that the major primate frugivores, rather than other arboreal frugivores, generated patterns of locally increased species richness around their preferred diet species (i.e. accumulator effects). More than half of the focal species showed accumulator effects with respect to species richness of small trees (<10 cm in diameter), but accumulator effects with respect to large trees were weak and not consistent with those of small trees. Primate‐dispersed focal species (but not hornbill‐ or other smaller bird‐dispersed species) showed significantly larger positive effect sizes than the remaining focal species. Synthesis . Our analysis suggests that primates—as major drivers of contagious seed dispersal—generate species‐rich seed rain around their preferred food‐tree species, which results in significantly larger local species richness of saplings. This is likely a consequence of heterospecific seed rain that reduces negative density dependence, and the presence of the accumulator pattern which persists at least until the large‐size stage. Hence, extirpation of primates may result in significant changes in the diversity and spatial structure of tropical forests. Abstract : Our analysis suggested that primates—as major drivers of contagious seed dispersal—generate species‐rich seed rain around their preferred food‐tree species, which results in significantly larger local species richness of saplings. This is likely a consequence of heterospecific seed rain that reduces negative density dependence, and the presence of the accumulator pattern which persists at least until the large‐size stage. Hence, extirpation of primates may result in significant changes in the diversity and spatial structure of tropical forests. The gibbon is foraging on one of the strongest accumulators, Nephelium melliferum (photo Kulpat Saralamba).